Farmgate versus market centre sales: a multi-crop approach - Benjamin Musah Abu; Haruna Issahaku; Paul Kwame Nkegbe (Agricultural and Food Economics, 2016)
Smallholder farmers have two basic decisions to make regarding selling their surplus produce: selling at farmgate at low prices or travelling to a market centre where higher prices are offered while incurring some transaction costs. Whichever decision is made has implications for poverty alleviation efforts. Previous studies have ignored modelling participation and market choice simultaneously. Taking a multi-crop approach, this paper fills the gap by investigating the key determinants of market participation decisions of smallholder farmers in Ghana using the sample selectivity probit model in order to account for potential endogeneity and selectivity bias and thus obtain unbiased estimates. Household survey data in the Upper West region of Ghana for the 2011 production season are used to achieve the goal of the study. The results reveal that yields of maize and groundnut and market information are the simultaneous determinants of market participation decisions while age of the farmer, yields of the two crops, membership of farmer organisation and prices of the two crops simultaneously determine the choice of market. These imply that policies that enhance productivity of these smallholders and market information are vital in the drive for a commercially oriented agriculture. Also, the incentives to incur transaction costs to market centres to benefit from remunerative prices lie in measures to increase yields.
Keywords: 330; Market participation; Smallholder farmers; Transaction costs; Sample selectivity probit; Ghana